PRINCIPLES OF DEVELOPMENT OF THE SPORTS SECTOR IN UZBEKISTAN - Abadan Ismailova (Proximus Journal Publishing, 2024)
On the basis of historical and legal documents, exact data there is represented chronological dynamics of development in the sphere of physical culture and sports, as well great achievements and major events sport movement of our country in the independent years.
Keywords: concept of renovation; reform; progress; modernization